Fusarium graminearum sensu stricto associated with head blight on rye (Secale cereal L.) in Argentina - Martínez, Mauro (2019)
Fusarium head blight (FHB) is one of the most important diseases that occurs in cereal regions worldwide and causes serious economic damage. This disease can be caused by several Fusarium species with Fusarium graminearum sensu stricto being the most common pathogen isolated from several crops. The aim of this study was to report the occurrence of F. graminearum sensu stricto on rye grains collected from field samples in Argentina and to determine the potential ability to produce deoxynivalenol (DON), nivalenol (NIV) and zearalenone (ZEA). Based on morphological characteristics, the isolate was identified as F. graminearum sensu stricto. To confirm molecularly, portions of the RED and TRI genes were sequenced and showed 99% similarity with the F. graminearum sensu stricto sequences available in the NCBI database. The potential to produce DON, 15-ADON and ZEA was determined. Moreover, Koch´s postulates were carried out. To our knowledge, this is the first report of F. graminearum sensu stricto associated with rye kernels in Argentina.